Uniform price auction of divisible goods based on multiple rounds linear bidding and its equilibrium analysis - Rao, Congjun; Zhao, Yong; Chen, Yang (Technological and Economic Development of Economy, 2015)
In this paper, the auction problem of a kind of continuous homogeneous divisible goods is studied and a uniform price auction mechanism is presented based on three conditions, i.e. the auctioneer’s supply is variable, every bidder submits multiple rounds continuous linear bidding, and every bidder’s valuation to per unit of the goods is independent private information. Concretely, two key problems, i.e. the bidders’ asymptotic strategic behaviours and forming process and composition of equilibrium points are explored. The conclusion is drawn that different bidders’ bidding order and different starting points of initial bidding would not cause different local equilibrium points, and if the equilibrium points exist, then the equilibrium point is unique.First published online: 09 Jun 2014